2023
DOI: 10.1002/ange.202300581
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Screening of Novel Infrared Nonlinear Optical Materials with High Thermal Conductivity: Long‐neglected Nitrides and Popular Chalcogenides

Abstract: Traditional infrared (IR) nonlinear optical (NLO) materials such as AgGaS 2 are crucial to key devices for solid-state lasers, however, low laser damage thresholds intrinsically hinder their practical application. Here, a robust strategy is proposed for unbiased highthroughput screening of more than 140 000 materials to explore novel IR NLO materials with high thermal conductivity and wide band gap which are crucial to intrinsic laser damage threshold. Via our strategy, 106 compounds with desired band gaps, NL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 101 publications
(2 reference statements)
1
4
0
Order By: Relevance
“…90,91 Other researchers using a hybrid functional, HSE06, calculated the bandgap to be 3.60 eV. 49 The absorption feature near 2.5 eV is similar to the 2.0 eV to 2.4 eV absorption onset reported for cation disordered Zn 3 MoN 4 and Zn 3 WN 4 synthesized as thin lms. 52,89 Computational work on similar materials has shown that localized, mid-gap electronic states arise when N atoms have Zn-rich coordination.…”
Section: Property Measurementssupporting
confidence: 55%
See 2 more Smart Citations
“…90,91 Other researchers using a hybrid functional, HSE06, calculated the bandgap to be 3.60 eV. 49 The absorption feature near 2.5 eV is similar to the 2.0 eV to 2.4 eV absorption onset reported for cation disordered Zn 3 MoN 4 and Zn 3 WN 4 synthesized as thin lms. 52,89 Computational work on similar materials has shown that localized, mid-gap electronic states arise when N atoms have Zn-rich coordination.…”
Section: Property Measurementssupporting
confidence: 55%
“…Synthesizing fullynitridized Zn-M-N (where M is a transition metal) in bulk would advance technologies in which thin lm nitrides have already shown promise, like photoelectrochemical energy conversion (ZnTiN 2 ), 47 transparent conducting oxides (ZnZrN 2 ), 48 and non-linear optics (Zn 3 WN 4 ). 49 Synthesizing Zn-M-N ternary nitrides via traditional methods is difficult. Many transition metals are highly refractory, meaning high temperatures would likely be needed for interdiffusion of reactants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, nitrides have garnered significant interest among researchers, and several nitrides have been investigated as NLO materials through experimental approaches and computational tools, such as Zn 2 NX (X = Cl, Br), MoZn 3 N 4 , TiZnN 2 and AGeN 2 (A = Sr, Ba). [30][31][32][33] However, NLO nitrides with outstanding properties remain scarce, and the structure-property relationships in NLO nitrides have not been thoroughly explored. Therefore, a comprehensive study of the characteristics and structure-property correlations in NLO nitrides is urgently needed.…”
Section: àmentioning
confidence: 99%
“…32 ZrZnN 2 crystalizes in the trigonal space group P3m1, in this structure, [ZrN 6 ] octahedra are connected by edge-sharing to build octahedral…”
mentioning
confidence: 99%